Analisis Bibliometrik Eksplorasi Etnomatematika - Sri Yulianti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This study aims to determine trends in ethnomathematics exploratory research and see research opportunities on connection capabilities in the future. This research uses bibliometric analysis method. The data in this study were obtained through Google Scholar from 2017 - 2022 with the keywords mathematical connection ability. Researchers analyzed 1000 original articles from 2017 - 2022. This study utilized PoP and VOSviewers software to analyze the data.